The hermeneutics of Torah Proverbs 2, Deuteronomy, and the composition of Proverbs 1-9 - Schipper, Bernd U. 1968- ([Erscheinungsort nicht ermittelbar] Society of Biblical Literature, 2021)
Cover -- Contents -- Preface -- Abbreviations -- Introduction -- Textual Analysis -- On the Tradition History of Proverbs 2 -- Proverbs 2 in the Context of the Book of Proverbs -- The Hermeneutics of Torah -- Conclusion -- Bibliography -- Ancient Sources Index -- Modern Authors Index.
Description based on publisher supplied metadata and other sources
Keywords: Bible; Electronic books